Overcoming resistance by ALK compound mutation (I1171S + G1269A) after sequential treatment of multiple ALK inhibitors in non‐small cell lung cancer - Takahashi, Ken (Thorac Cancer, 2020)
BACKGROUND: Anaplastic lymphoma kinase (ALK) fusion genes are found in 3%–5% of non‐small cell lung cancers (NSCLCs). ALK inhibitors show a very high response rate to ALK‐positive NSCLCs. However, the emergence of acquired resistance is inevitable. In this study, we investigated the drugs for overcoming resistance especially compound mutations after sequential treatment with crizotinib, alectinib, and lorlatinib. METHOD: Next‐generation sequencing (NGS) and Sanger sequencing were performed on a liver biopsy tissue obtained from a clinical case. Ba/F3 cells in which mutant EML4‐ALK were overexpressed were prepared, and cell viability assay and immunoblotting were performed to check the sensitivity of five independent ALK inhibitors. RESULTS: I1171S + G1269A double mutation was identified by NGS and Sanger sequencing on a liver biopsy tissue from a patient who relapsed on lorlatinib treatment. Ceritinib and brigatinib—but not other ALK inhibitors—were active against the compound mutations in the cell line model. CONCLUSIONS: With the sequential ALK inhibitors treatment, cancer cells accumulate new mutations in addition to mutations acquired previously. The identified compound mutation (I1171S + G1269A) was found to be sensitive to ceritinib and brigatinib, and indeed the patient's tumor partially responded to ceritinib. KEY POINTS: ALK compound mutation was found in a clinical sample that was resistant to lorlatinib after sequential ALK‐tyrosine kinase inhibitor (TKI) treatment. Ceritinib and brigatinib are potential overcoming drugs against ALK I1171S + G1269A double mutation.